Using blogs for facilitating and connecting nurse educator candidates - Papastavrou, Evridiki; Hamari, Lotta; Fuster, Pilar; Istomina, Natalja; Salminen, Leena Kaarina (My University, 2016)
Background Social media includes blog applications, which can be used as online journals or diaries that encourages interaction and collaboration within an online community. The aim of this study was to explore and describe the use of blog writing as learning journals during a short course for nurse educator candidates about social media. Method A qualitative descriptive design was used. The participants were nurses, Bachelor, Master's and Doctoral students who intended to follow a career in education (N = 24, female n = 21, male n = 3, Mean age 37) from four different countries of the European Union. The blogs written during the course were used as a data collection method and the data was analyzed with qualitative content analysis. Results A total of 260 blogger posts and 372 peer comments were analyzed. Four main categories emerged from the analysis: 1) Course content, new knowledge, and changed views, 2) Reflection and critical thinking, 3) Encouraging and peer support and 4) Expressing feelings, experiences, and expectations. Conclusion Blogs are potential learning spaces in short courses in nurse educator education, especially in sharing feelings and experiences, enhancing an encouraging atmosphere, critical thinking, and reflection.
Keywords: Blog analysis; Blogging; Nurse educator candidate; Qualitative descriptive study; Social media